A first overview of ant diversity in mangroves along the Ecuadorian coast - Marissa Barreno; Myriam Arias de López; Natalia Molina-Moreira; Alex Pazmiño-Palomino (Revista Brasileira de Entomologia)
ABSTRACT The mangroves along the Pacific coastline of South America are considered highly vulnerable ecosystems due to resource exploitation and climate change; nevertheless, they remain largely ignored. This study focuses on an overlooked aspect of an understudied ecosystem: mangrove ant fauna. We describe the ant diversity from eight mangrove forests along the Ecuadorian coast. A total of 400 occurrences were recorded, representing 31 species, 16 genera, and 5 subfamilies. Myrmicinae was the most abundant subfamily, comprising 64% of the samples, with the genus Crematogaster being dominant. We also provide brief diagnoses and general comments on the most important species. Two species, Camponotus dalmasi Forel and Crematogaster ampla Forel, are recorded for the first time in Ecuador. Additionally, four exotic species with global distributions are documented: Monomorium floricola Jerdon, Paratrechina longicornis Latreille, Tetramorium bicarinatum Nylander, and Tapinoma melanocephalum (Fabricius). We discuss the potential causes and impacts of these species' presence on mangrove ecosystems. Our work contributes to the first efforts to study mangrove myrmecofauna on the Pacific coast of South America, emphasizing the need to increase research, conservation, and restoration efforts for this threatened ecosystem and its components.